Management Skills of Professional Engineers in the Industry and the Academe in the Samar Island: Basis for Formulating a Management Manual - Balanlay, Jr., Bienvinido (JPAIR Multidisciplinary Research, 2020)
The study was conducted to determine the management skills of professional engineers in the industry and in the academe in the Samar Island: basis for formulating a management manual. The personality traits among the five factors ‘conscientiousness’ was more dominant and were rated as 'high extent. Problem-solving skills were rated ‘very good,’ and management performance was rated ‘very satisfactory.’ The relationship between socio-demographic profile and management skills, in terms of administrative and leadership skills, were found 'significant.’ The relationship between socio-demographic profile and management performance, planning, and controlling were found 'significant.’  The relationship between personality traits and management skills, leadership, and problem-solving skills dominate and were highly significant in management skills. At the same time, conscientiousness and agreeableness were highly ‘significant’ in personality traits. Between personality traits and management performance: openness – planning, directing, and influencing; conscientiousness – planning; extraversion – directing; in agreeableness – planning and influencing were found significantly related, and in neuroticism – all parameters were found ‘not significant.’ Test difference in management skills and performance between professional engineers in industry and academe; conceptual skills were found ‘significant.’
Keywords: Engineering; Personality Traits; Management Skills; Management Performance; descriptive-correlational method; Philippines